2014
DOI: 10.1093/ntr/ntu165
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Cigarette Smoking Initiation in Jordanian Schoolchildren: Longitudinal Analysis

Abstract: This study shows that many Jordanian youth have an intention to initiate cigarette smoking and are susceptible to cigarette smoking modeled by peers and that girls are influenced as well by familial cigarette smoking. Prevention efforts should be tailored to address culturally relevant gender norms, help strengthen adolescents' self-efficacy to refuse cigarettes, and foster strong non-smoking social norms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 82 publications
3
23
1
Order By: Relevance
“…Twenty five percent (25%) students reported that since their friends smoked they took up smoking as part of their social interaction, 21% of smokers said that it was easy availability of cigarettes in market which encourage them to smoke, 12% respondents stated movies a reason of taking up cigarette smoking, only 4.5% stated parents and family a reason to start smoking, this value is much less than other studies, 7% students were stating advertisements a reason to smoke and 7% stated curiosity, these reasons were similar to previous studies with a slight difference in percentages (4,5,29,(36)(37)(38).…”
Section: Determinantssupporting
confidence: 74%
See 1 more Smart Citation
“…Twenty five percent (25%) students reported that since their friends smoked they took up smoking as part of their social interaction, 21% of smokers said that it was easy availability of cigarettes in market which encourage them to smoke, 12% respondents stated movies a reason of taking up cigarette smoking, only 4.5% stated parents and family a reason to start smoking, this value is much less than other studies, 7% students were stating advertisements a reason to smoke and 7% stated curiosity, these reasons were similar to previous studies with a slight difference in percentages (4,5,29,(36)(37)(38).…”
Section: Determinantssupporting
confidence: 74%
“…Regardless of negative impacts substance is always used by youth, use of psycho active substance like tobacco products, alcohol beverages and marijuana have become major public health issues (2). Substance use in students is associated with many different factors like peer pressure, age, sex, personal pleasure, family substance abuse and poor academic achievement (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Of research examining gender and tobacco, multiple articles focused on men and highlighted that smoking cessation programs can be successful by encouraging positive masculine ideas such as responsibility and fatherhood [4043]. There was also research suggesting increasing gender equality by challenging traditional gender norms may encourage women to engage in unhealthy behaviors like smoking [44] and problematic drinking [45, 46]. Specifically, women who endorse more equitable roles for men and women may adopt what they view as traditionally masculine behaviors as a means of demonstrating parity.…”
Section: Gender and Health Behaviorsmentioning
confidence: 99%
“…Like cigarettes, it is necessary to know the percentage of waterpipe experimenters who will continue to smoke waterpipe. Additionally, understanding the factors that distinguish adolescents who progress in waterpipe smoking beyond the experimentation stage is crucial for early intervention before the development of nicotine dependence that is manifested by the increased frequency of waterpipe use (Salameh et al, 2008), or the onset of cigarette smoking (Jaber et al., 2015; Mckelvey et al, 2014). …”
Section: Introductionmentioning
confidence: 99%